FAKTOR-FAKTOR PENENTU CAPITAL ADEQUACY RATIO - Ary Satria Pamungkas; Debby Arthur Harris (Jurnal Manajemen., 2014)
This study was aimed to investigate the influence of risk, management quality, bank size and bank liquidity to Capital Adequacy Ratio. The sample in this study are publicly traded banks listed on the Indonesian Stock Exchange for the period 2008-2010. Multiple regression analysis method was used to analyze the data. The results of this study is that there is the influence of risk, management quality, bank size and bank liquidity to Capital Adequacy Ratio simultaneously.